Analysis of the expression of PIWI-interacting RNAs during cardiac differentiation of human pluripotent stem cells - la Greca, Alejandro Damián (2020)
PIWI-interacting RNAs (piRNAs) are a class of non-coding RNAs initially thought to be restricted exclusively to germline cells. In recent years, accumulating evidence has demonstrated that piRNAs are actually expressed in pluripotent, neural, cardiac and even cancer cells. However, controversy remains around the existence and function of somatic piRNAs. Using small RNA-seq samples from H9 pluripotent cells differentiated to mesoderm progenitors and cardiomyocytes we identified the expression of 447 piRNAs, of which 241 were detected in pluripotency, 218 in mesoderm and 171 in cardiac cells. The majority of them originated from the sense strand of protein coding and lncRNAs genes in all stages of differentiation, though no evidences for secondary piRNAs (ping-pong) were found. Genes hosting piRNAs in cardiac samples were related to critical biological processes in the heart, like contraction and cardiac muscle development. Our results indicate that somatic piRNAs might have a role in fine-tuning the expression of genes involved in differentiation of pluripotent cells to cardiomyocytes.